Tool life modeling in high speed turning of AISI 4340 hardened steel with mixed ceramic tools by using face central cubic design - Al Hazza, Muataz Hazza Faizi; Adesta, Erry Yulian Triblas; Hassan, Muhammad Hasibul (Department of Electrical Engineering and Information Technology (DIETI), FEDERICO II University, 2013)
Tool life estimation for the cutting tool before the machining process is important due to economic and quality consideration. Thus, developing a model that can predict the tool life with high accuracy is an important issue. This paper deals with developing a new model of tool life for mixed ceramic tools in turning hardened steel AISI 4340 based on experimental tests. The experiments were planned and implemented using Central Composites Design (CCD) of Response Surface Methodology (RSM) with three input factors: cutting speed, feed rate and negative rake angle. The Face Central Cubic Design has been used as a special case of CCD. The analysis of variance (ANOVA) has been conducted to analyze the influence of process parameters and their interaction during machining. The first and second order models have been developed. It was found that the second order model provide higher accuracy prediction than the first order model. It was observed that the cutting speed is the most significant factor that influences the tool life for the two models, followed by the feed rate then the negative rake angle. The predicted values are confirmed by using validation experiments. Copyright © 2013 Praise Worthy Prize S.r.l. - All rights reserved.